2017
DOI: 10.1038/npp.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Singular Location and Signaling Profile of Adenosine A2A-Cannabinoid CB1 Receptor Heteromers in the Dorsal Striatum

Abstract: The dorsal striatum is a key node for many neurobiological processes such as motor activity, cognitive functions, and affective processes. The proper functioning of striatal neurons relies critically on metabotropic receptors. Specifically, the main adenosine and endocannabinoid receptors present in the striatum, ie, adenosine A2A receptor (A2AR) and cannabinoid CB1 receptor (CB1R), are of pivotal importance in the control of neuronal excitability. Facilitatory and inhibitory functional interactions between st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 63 publications
1
40
2
Order By: Relevance
“…The A 2A R‐CB1R form heteromeric complexes and recent studies revealed that the complex becomes dysfunctional in caudate putamen of advanced HD patients (Moreno et al . ).…”
Section: Changes In the Endocannabinoid System In Neurodegenerative Dmentioning
confidence: 97%
See 1 more Smart Citation
“…The A 2A R‐CB1R form heteromeric complexes and recent studies revealed that the complex becomes dysfunctional in caudate putamen of advanced HD patients (Moreno et al . ).…”
Section: Changes In the Endocannabinoid System In Neurodegenerative Dmentioning
confidence: 97%
“…Along with CB1R, adenosine A 2A receptor (A 2A R) plays an important role in the control of neuronal excitability. The A 2A R-CB1R form heteromeric complexes and recent studies revealed that the complex becomes dysfunctional in caudate putamen of advanced HD patients (Moreno et al 2017).…”
Section: Ec System In Huntington's Diseasementioning
confidence: 97%
“…A 1 receptors are expressed ubiquitously in the brain while A 2A receptors are primarily expressed in the striatum and olfactory tubercle [Dunwiddie & Masino, 2001]. Further, A 2A receptors in the striatum are almost exclusively expressed postsynaptically in striato-pallidal neurons of the indirect pathway [Moreno et al, 2017]. It has been shown that stimulation of adenosine A 2A receptors can counteract the inhibitory effects of dopamine D 2 receptors on striatal indirect pathway neurons [Nair, Gutierrez-Arenas, Eriksson, Vincent, & Hellgren Kotaleski, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils from HD patients have higher A 2A receptor dysfunction in homozygous vs. heterozygous HD patients while no changes in A 1 or A 3 receptors are observed in peripheral blood cells (Varani et al, 2003). A 2A -cannabinoid CB1 receptor heterodimers exert crucial function by controlling neuronal excitability (Moreno et al, 2017), while activation of striatal A 2A receptors may inhibit CB1 function independent from heterodimer formation (Ferreira et al, 2015). Patients harboring high-grade HD do not possess A 2A -CB1 receptor heterodimers in the caudate-putamen region due to the lack of CB1 receptors (Moreno et al, 2017).…”
Section: Purinergic Involvement In Hd Adenosine Receptormentioning
confidence: 99%
“…A 2A -cannabinoid CB1 receptor heterodimers exert crucial function by controlling neuronal excitability (Moreno et al, 2017), while activation of striatal A 2A receptors may inhibit CB1 function independent from heterodimer formation (Ferreira et al, 2015). Patients harboring high-grade HD do not possess A 2A -CB1 receptor heterodimers in the caudate-putamen region due to the lack of CB1 receptors (Moreno et al, 2017). Recent evidence suggests that consuming more than 190 mg/day of caffeine may accelerate HD onset (Simonin et al, 2013), contradicting findings in animal models that point toward beneficial effects of A 2A receptor antagonism in HD.…”
Section: Purinergic Involvement In Hd Adenosine Receptormentioning
confidence: 99%